Work Stress Levels and Safety Procedure Compliance among Traditional Gold Miners - Surahmi; Alfunnafi Fahrul Rizal (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Work-related stress is an occupational health problem that can influence workers’ behavior, including compliance with safety procedures. Traditional gold miners work in high-risk environments that may increase stress and reduce awareness of occupational safety practices. This study aimed to determine the relationship between work stress level and compliance with occupational safety procedures among traditional gold miners. This study used an analytical observational design with a cross-sectional approach. The sample consisted of 75 traditional gold miners selected using a total sampling technique based on inclusion and exclusion criteria. Data were collected using questionnaires consisting of respondent characteristics, work stress level, and compliance with occupational safety procedures. The data were analyzed using univariate analysis and bivariate analysis with the Chi-Square test. The results showed that most respondents experienced moderate work stress and most respondents were non-compliant with occupational safety procedures. The statistical analysis showed a significant relationship between work stress level and compliance with occupational safety procedures among traditional gold miners. Workers with higher stress levels tended to have lower compliance with safety procedures. Therefore, work stress management, occupational safety education, and regular supervision are needed to improve compliance with safety procedures among traditional gold miners.